Natural fermentation quality, bacteria, and functional profiles of three cuttings of alfalfa silage in a year in Inner Mongolia, China - Sun, Juanjuan; Wang, Jing; Bai, Chunsheng; Zhao, Jinmei; Yun, Ying; Yu, Zhu; Xue, Yanlin; Zhang, Tengwei; Bao, Wenlong (Frontiers in Microbiology, 2023)
Alfalfa is harvested two or three times a year in central and western Inner Mongolia, China. However, the variations in bacterial communities as affected by wilting and ensiling, and the ensiling characteristics of alfalfa among the different cuttings, are not fully understood. To enable a more complete evaluation, alfalfa was harvested three times a year. At each time of cutting, alfalfa was harvested at early bloom, wilted for 6 h, and then ensiled in polyethylene bags for 60 days. The bacterial communities and nutritional components of fresh alfalfa(F), wilted alfalfa(W) and ensiled alfalfa(S), and the fermentation quality and functional profile of bacterial communities of the three cuttings alfalfa silage, were then analyzed. Functional characteristics of silage bacterial communities were evaluated according to the Kyoto Encyclopedia of Genes and Genomes. The results showed that all nutritional components, fermentation quality, bacterial communities, carbohydrate, amino acid metabolism and key enzymes of bacterial communities were influenced by cutting time. The species richness of F increased from the first cutting to the third cutting; it was not changed by wilting, but was decreased by ensiling. At phylum level, Proteobacteria were more predominant than other bacteria, followed by Firmicutes (0.063–21.39%) in F and W in the first and second cuttings. Firmicutes (96.66–99.79%) were more predominant than other bacteria, followed by Proteobacteria (0.13–3.19%) in S in the first and second cuttings. Proteobacteria, however, predominated over all other bacteria in F, W, or S in the third cutting. The third-cutting silage showed the highest levels of dry matter, pH and butyric acid (p < 0.05). Higher levels of pH and butyric acid were positively correlated with the most predominant genus in silage, and with Rosenbergiella and Pantoea. The third-cutting silage had the lowest fermentation quality as Proteobacteria were more predominant. This suggested that, compared with the first and second cutting, the third cutting is more likely to result in poorly preserved silage in the region studied.